From despair to hope HOPE VI and the new promise of public housing in America's cities - Cisneros, Henry; Engdahl, Lora.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2009)
"Documents the evolution of HOPE VI, exploring what it accomplished replacing severely distressed public housing with mixed-income communities and where it fell short. Reveals how a program conceived to address a specific problem triggered a revolution in public housing and solidified principles that still guide urban policy today"--Provided by publisher.
Foreword / Kurt L. Schmoke -- Acknowledgements -- Program origins and defining principles -- A new moment for people and cities / Henry Cisneros -- The origins of HOPE VI / Bruce Katz -- The evolution of HOPE VI as a development program / Richard D. Baron -- HOPE VI and the new urbanism / Peter Calthorpe -- HOPE VI and the deconcentration of poverty / Alexander Polikoff -- Setting the stage : early HOPE VI redevelopments -- An overview of HOPE VI revitalization grant projects / Lora Engdahl -- New Holly, Seattle / Lora Engdahl -- The villages of Park DuValle, Louisville / Lora Engdahl -- Broader impacts of the model -- The Atlanta blueprint : transforming public housing citywide / Renee Lewis Glover -- HOPE VI, neighborhood recovery, and the health of cities / Margery Austin Turner -- Has HOPE VI transformed residents' lives? / Susan J. Popkin and Mary K. Cunningham -- How HOPE VI has helped reshape public housing / Richard C. Gentry -- Learning from critiques and planning for the future -- HOPE VI : what went wrong / Sheila Crowley -- The conservative critique of HOPE VI / Ronald D. Utt -- Taking advantage of what we have learned / G. Thomas Kingsley -- Appendix A. Scope and status of the HOPE VI program / G. Thomas Kingsley -- Appendix B. HOPE VI revitalization program grants 1993-2008 -- Contributors.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Public housing -- United States -- Finance; Housing policy -- United States; Housing rehabilitation -- United States; Urban renewal -- United States; Electronic books